The Validity of E-Rickshaws: A Contractual and Regulatory Deconstruction (Maharaja Surajmal Institute Law Journal, 2026)
The paper examines critically the Indian e-rickshaw sector by analyzing the  regulatory framework governing it, drawn from key judicial interventions  around its registration,licensing, insurance, and safety compliance. It further  discusses how contract law applies to daily passenger-driver interactions by  setting up implied duties of safety, care, and fairness. Finally, the study also  evaluates the innovative Battery as a Service model, being a hybrid contractual  approach with impact on the reliability of the vehicle. The central argument  isthat the true legitimacy of the e-rickshaw sector relies on the robust inter play between itslegal regulations, contractual relationships, and technological standards. Only through the coordinated strengthening of these elements  can e-rickshaws be integrated as a safe, lawful, and sustainable component of  India’s urban transport landscape.
Keywords: E-rickshaws; Electric mobility; Motor Vehicles (Amendment) Act; Regulatory compliance; Urban transport law; Contract of carriage; Sale of Goods Act; 1930; Product liability; Battery-as-a-Service (BaaS)